The determinants of intention to stay at Cameron Highland’s homestay among young domestic tourists - Ha Haw Seng; Nurul Aisyah Samsudin; Fatin Fasihah Mokhtar; Wan Amirah Shahirah Wan Husain (2021)
Nowadays, Homestay is a common type of hospitality and accommodation in which visitors share a residence with a resident of the city they are travelling to. There have a lot of aspect that determination of the intention to stay at Cameron Highlands’ homestay among young domestic tourists. The homestay service become one of aspect that affecting the intention of young domestic tourists. Therefore, this study, namely the determinants of intention to stay at Cameron Highland's homestay among young domestic tourists. This study has selected a sample size of 384 sets of respondents from residents who are young domestic tourists in Malaysia. The quantitative research using online questionnaire distributed through Facebook, WhatsApp, and Telegram. This study uses non-probability sampling methods and convenient sampling of selected samples. After that, SPSS would use to analyses the collecting data by using the descriptive analysis, reliability test, and Pearson correlation. The result show that all of the independent variable (enjoyment, social benefit, economic benefits, and locational benefits) has a significant relationship with the dependent variable intention to stay at Cameron Highland’s homestay among young domestic tourists.